An X-ray photoelectron spectroscopy study of ionic liquids based on a bridged dicationic moiety. Issue 2 (April 2022) - Zafar, Anham; Evans, Tim; Palgrave, Robert G; ud-Din, Imtiaz-
A series of imidazolium and pyridinium-based bridged dicationic ionic liquids have been analysed using X-ray photoelectron spectroscopy. The different electronic environments of the dications have been investigated and a robust fitting model for the carbon C1s region has also been developed. The relative positions of different C1s components and N1s of dications have been determined and their complex C1s photoemission spectra produced from both aromatic and aliphatic carbon states giving photoemission peaks in the binding energy range of 289.0–283.9 eV. A contemporary fitting approach has been applied to a different set of environments which allowing comparison of the binding energies of cationic components of imidazolium and pyridinium-based dicationic ionic liquids. The experimental stoichiometry of all the carbons and nitrogens have also been calculated from XP spectra of the dicationic ionic liquids.